Evaluasi Keandalan Sistem Distribusi Tenaga Listrik Berdasarkan Indeks Keandalan SAIDI dan SAIFI pada PT PLN (PERSERO) Rayon Kefamenanu - Funan, Frederikus; Sutama, Wayan (Jurnal Ilmiah Telsinas, 2020)
The development of the number of customers in PT PLN (Persero) Rayon Kefamenanu increases every year. PT PLN (Persero) As a power supply company must be able to meet the electricity distribution to customers continuously. In preliminary observations of customers at PT PLN (Persero) Rayon Kefamenanu often experienced blackouts both in the number of outages and a long outage. This outage will result in losses for both the customer and PLN itself, so it is necessary to study the reliability of the distribution network system by calculating SAIFI and SAIDI.From the calculation of the SAIFI and SAIDI index values in 2017, 2018 and 2019, a comparison is made with the SPLN 68-2: 1986 standard values as follows: For the SAIFI reliability index values in 2017, 2018 and 2019 when compared to the SPLN 68-2: 1986 standards with the maximum value of the SAIFI standard of 3.2 times / customer / year is categorized as not reliable because the magnitude of the SAIFI count exceeds the SPLN 68-2: 1986 standard. For the SAIDI reliability index values in 2017, 2018 and 2019 when compared to the SPLN 68-2 standard : 1986 with a maximum value of SAIDI standard of 21.09 times / customer / year there is 2019 categorized reliable because the SAIDI calculation value is smaller than the SPLN standard value of 68-2: 198 and 2017 and 2018 are categorized as not reliable due to the magnitude of SAIDI calculated Exceeds SPLN 68-2: 1986 standards.While the large number of kwh losses that were not channeled due to disruptions that occurred in 2017, 2018 and 2019 at PT. PLN (Persero) Kefamenanu Rayon is: The value of ENS (Energy Not Served) in 2017 of 24,866.1 kwh or a cost loss of Rp 36,485,513,208. The value of ENS (Energy Not Served) in 2018 is 17,122.37 kwh or a loss in cost of Rp.25,123,311,0536. The value of ENS (Energy Not Served) in 2019 is 10,402.45 kwh or a loss in costs is Rp 15,263,306,836.